Pengembangan media pembelajaran berbasis artificial intelligence sesuai karakteristik perkembangan anak usia dini - Wahyu Cinta Nur Aini (Universitas PGRI Madiun, 2026)
The purpose of early childhood education is to prepare children for the next level of education. This study examines the role of Artificial Intelligence (AI) as a learning medium in Early Childhood Education (ECE), which plays an important role in building a comprehensive foundation for children's development. The discussion focuses on the use of AI in creating adaptive, interactive, and responsive learning environments that accommodate the individual needs of children, including physical and motor, cognitive, social-emotional, language, and moral development. This study employs a literature review method by examining books, scientific articles, national journals, and other relevant academic sources related to the application of AI in early childhood education. The collected data were analyzed descriptively to identify concepts, findings, and developments in previous studies. The results of the review indicate that AI is effective in providing personalized learning experiences tailored to children's developmental levels and individual needs. Furthermore, AI supports the development of social skills through interactive learning media and enhances children's learning motivation by providing engaging and interactive learning experiences. The findings suggest that AI-based learning media can stimulate children's thinking, emotions, attention, and competencies. AI also enables more dynamic content delivery and assists educators in designing more effective teaching strategies. Therefore, the use of AI-based technology as a learning medium makes a significant contribution to improving the quality and effectiveness of learning in early childhood education.